Comparative geochemistry of three urban streams in Athens: Kifissos-Podoniftis-Pikrodafni - Argyraki, A.; Paraskos, F.; Marmara, M.; Papadopoulou, K.; Maglaropoulou, A. (Bulletin of the Geological Society of Greece, 2013)
The geochemistry of three urban streams in Athens was analysed and compared on the basis of major elements and heavy metals content in water and active sediment. The studied streams of Kifissos, Podoniftis and Pikrodafni run through the Athens basin of a total area of 540 km2 but differ with respect to the origin of their headwaters i.e., Parnitha, Penteli and Hymettus mountains. The main aim of the study was to determine the geochemical signature of water and sediment within the Athens hydrological basin and evaluate the effect of natural and anthropogenic environment on these water courses. A total of 56 stream water samples were obtained and analysed for major anions, cations and heavy metals (Mn, Cr, Cu, Zn, Pb) as well as nitrate and phosphate concentrations. Active stream sediments were collected at 22 locations along the streams and were analysed for heavy metals (Pb, Zn, Cu, Mn, Cr, Ni, Cd). Results indicated that rock weathering, rather than atmospheric or pollution influx is the dominant process affecting the major ion geochemistry of stream flow in the urban setting. However, Kifissos and Podoniftis waters had higher nitrate and phosphate concentrations indicating greater influence by anthropogenic activities. In general the quality characteristics of water and sediment in the study area were found to be in a good state regarding the studied parameters.